ANALISIS KETERAMPILAN KOMUNIKASI SISWA PADA MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) BERBANTUAN GAMIFIKASI - Khumaidah, Nabillatul; Qomaria, Nur; Yamin, Yamin; Hartiningsih, Try; Hadi, Wiwin Puspita (Natural Science Education Research, 2023)
This research aims to determine the effect of the Numbered Head Together (NHT) learning model with gamification on students' communication skills. The research method used is quasi-experimental with a non-equivalent control group design, conducted at SMPN 24 Gresik in the academic year 2022/2023. Data collection techniques were done through tests and documentation with a population of seventh-grade students and a sample consisting of Class VII A as the control group and Class VII D as the experimental group using Random Sampling. Hypothesis testing was conducted using the non-parametric Mann-Whitney U test. The research results showed that: 1) in the communication skills test, a significance value of 0.001 less than 0.005 was obtained, indicating the rejection of H0, 2) the improvement in the experimental class was measured with an N-Gain of 0.78, categorized as high